A cross sectional study of the proximal femur morphology of the normal malay population using computed tomography images (scanogram) at HUSM - Dzuraimy, Ismail (2008)
A cross sectional study on the morphometry of proximal femur in Malay patients who were treated in Hospital Universiti Sains Malaysia. Objectives To quantify the proximal femur dimensions in Malay patients, to compare the parameters between male and female patients and to determine the correlation between the parameters. Summary of the Background Data Previous studies have shown a significantly smaller proximal femur parameters in the Asian population compared to Caucasian population. Currently used proximal femur implants size were based on Caucasian studies. However, due to the smaller size of proximal femur in Asian population, improvement in the design of implant are required to optimize component fixation and to restore the normal biomechanics of the hip joint. Methods Proximal femoral bones were studied in 140 patients ( 70 male and 70 female ) who had undergone computerized tomographic scan for various pelvic pathology but with normal proximal femur morphology. The age range was between 18 to 80 years old. The VII following parameters were studied : 1) Femoral neck shaft angle, 2) Femoral head diameter, 3) Femoral neck isthmus diameter, 4) Vertical offset of femur, 5) Horizontal offset of femur. The data obtained were statistically analyzed using independent T -test to determine the differences between male and female patients. The mean of all the parameters of current study were compared with published Western and Asian studies using one sample T -test. Significant differences for all the statistical test were set at p < 0.05. Results There were significant differences between male and female patients in femoral head diameter, femoral neck isthmus diameter, vertical offset and horizontal offset. However, there was no significant difference in neck shaft angle. Female patients have significantly smaller dimensions in all the parameters measured except for neck shaft angle which was larger. When the observations in the current study was compared to radiographic study by Sugano et al and Noble et al, significant differences were found in head diameter, neck isthmus diameter, vertical offset and neck shaft angle. The head diameter, neck isthmus diameter and vertical offset of the current study were significantly smaller compared to their study. However the neck shaft angle of the current study was significantly larger than their study. Vlll Conclusions The current study have shown that the proximal femur morphometry of Malay population was smaller compared to Caucasian and Thai population.